Representation of Peace Values in an Indonesian EFL Textbook: A Critical Discourse Analysis - Nariza Ayu Pasha; Ikmi Nur Oktavianti; Muzni Muslim (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
Violence, bullying, and crime in schools have become prevalent issues in Indonesia, with the government and educational institutions actively working to prevent these behaviors. Peace values, which can be taught through textbooks, play a crucial role in this effort. Despite the implementation of Kurikulum Merdeka, no research has explicitly examined the representation of peace values in the English textbooks published by the Indonesian Ministry of Education and Culture, Research, and Technology. The study investigates the representation of peace values in the English for Nusantara textbook for Junior High Schools. Using Critical Discourse Analysis by Fairclough, the study found that the textbook represents three types of peace values, textually and visually: inner peace, social peace, and peace with nature. However, these values are still represented disproportionately. In practice, this research can be used for English teachers in selecting, designing, and evaluating learning materials which represent the peace values suitably to students. Apart from that, it could be a reference for book authors to develop materials which are balanced in presenting peace values according to Indonesian students' requirements. In addition, this study can be an alternative for the government in curricula design and evaluation.